Karakterisasi Kekuatan Lelah Siklus Rendah Besi Cor Kelabu: Characterization of Low Cycle Fatigue Strength of Gray Cast Iron - Agus Suprihanto; Dwi Basuki Wibowo; Djoeli Satrijo (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2019)
Low cycle fatigue testing has been carried out on gray cast iron. 60 specimens made of three FC200 gray cast iron alloys with Cr (0.23%, 0.32% & 0.47% wt) and Cu (0.6% -0.7%) were tested using a servo pulse machine. Specimen dimensions refer to ASTM E739 standard. Low cycle fatigue testing used strain amplitudes between 0.15 to 0.5%. The fatigue behavior is characterized using Downing and Fash method. The analysis shows that the coefficient of fatigue strength (A) is between 2.336 –2.896 and the exponent of fatigue strength is between -0.251 to –0.266.